The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3390/ph3072291
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs and the Kidney

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) inhibit the isoenzymes COX-1 and COX-2 of cyclooxygenase (COX). Renal side effects (e.g., kidney function, fluid and urinary electrolyte excretion) vary with the extent of COX-2-COX-1 selectivity and the administered dose of these compounds. While young healthy subjects will rarely experience adverse renal effects with the use of NSAIDs, elderly patients and those with co-morbibity (e.g., congestive heart failure, liver cirrhosis or chronic kidney disease) and dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(201 citation statements)
references
References 220 publications
8
170
0
6
Order By: Relevance
“…Diclofenac sodium probably causes a decrease in glomerular filtration rate, resulting in decreased excretion of urea, which may produce an increase in the concentration of the blood urea . It was earlier reported that diclofenac inhibits cyclooxygenases, thereby suppressing the production of prostaglandins, which play an important role in maintaining glomerular filtration rate of the kidneys (Hörl, 2010;Dhanvijay et al, 2013). Creatinine is a nonprotein nitrogenous substance formed from creatine and phosphocreatine during muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diclofenac sodium probably causes a decrease in glomerular filtration rate, resulting in decreased excretion of urea, which may produce an increase in the concentration of the blood urea . It was earlier reported that diclofenac inhibits cyclooxygenases, thereby suppressing the production of prostaglandins, which play an important role in maintaining glomerular filtration rate of the kidneys (Hörl, 2010;Dhanvijay et al, 2013). Creatinine is a nonprotein nitrogenous substance formed from creatine and phosphocreatine during muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…They exert their anti-inflammatory, antipyretic and analgesic effects via the suppression of prostaglandins (PGs) synthesis, by inhibiting the enzyme, cyclooxygenase (COX), which has two isoforms, COX-1 and COX-2 (Hörl, 2010). They inhibit both COX-1 and COX-2, the rate-limiting enzymes for the production of prostaglandins and thromboxane (Harris, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in clearance of meloxicam when given in combination with erlotinib might be due to the extensive metabolism of both the drugs by liver as explained by Busch et al, (1998) and as well as the enzyme involved in metabolism of both drugs like CYP3A4, CYP3A5, CYP1A1, CYP1A2 and CYP2C9 as reported by Meineke and Turck (2003) and Li et al, (2007 b ). It is also reported by Busch et al, (1998) that 60-65 % metabolite of meloxicam are being excreted through kidney whereas meloxicam may decrease the blood flow to kidney (Horl, 2010), which may be the reason of low clearance rate. The smaller value of volume of distribution in present study is typical of the class NSAIDs which may be due to higher plasma protein biding of meloxicam (Turck et al, 1996).…”
Section: Resultsmentioning
confidence: 83%
“…PGE 2 and PGI 2 or formation of deacetylated products of paracetamol i.e., p-aminophenol and p-phenoxy free radical or both. 34,41,42 In the study, we found that the test drug i.e., among N. sativa extracts (ethanolic and aqueous) showed a protective effect against paracetamol-induced damages in the kidney. Although, all the test groups showed nephroprotective effect in a dose-dependent manner but the maximum protection was shown by NSEE (400 mg/kg p.o) as evidenced by significant decrease in serum creatinine and blood urea levels as compared to negative control group (p<0.001).…”
Section: 39mentioning
confidence: 98%